Evil bones - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series, 2025)
"Small creatures--a rat, a rabbit, a squirrel--have been turning up throughout Charlotte, North Carolina, mutilated and displayed in a bizarre manner. But one day, as Tempe is relaxing at home alongside her aimless, moody great-niece Ruthie, she's diverted by a disturbing call. The perp is upping the ante. This find could be human. Tempe visits the scene and discovers that the victim is a dog. Someone's pet. As one who has always found animal cruelty abhorrent, Tempe agrees to help apprehend the person responsible, and she acquires an equally outraged ally in semi-retired homicide detective Erskine 'Skinny' Slidell. Needing a better understanding of possible motives, Tempe seeks input from a forensic psychologist. The doctor has no definitive answer but offers several possibilities, warning that the escalating pattern of aggression suggests even more macabre discoveries--and a shift in the perp's focus to humans. And then it happens. A woman is found disfigured and posed in a manner that mimics the animal killings. Subsequently, people Tempe cares about begin to go missing until it becomes clear she is being taunted, the target in a sick game that has her and Slidell racing against a ticking clock and facing a terrifying question: 'What is pure evil?'"--